2018
DOI: 10.1016/j.ygcen.2018.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Roles of progesterone receptor membrane component 1 and membrane progestin receptor alpha in regulation of zebrafish oocyte maturation

Abstract: Although previous studies suggest membrane progesterone receptor alpha (mPRα/Paqr7) mediates 17, 20β-dihydroxy-4-pregnen-3-one (DHP) induction of oocyte maturation (OM) in zebrafish, critical information needed to establish mPRα as the receptor mediating OM is lacking. The relative potencies of progestins and specific mPRα agonists in inducing OM matched their relative binding affinities for zebrafish mPRα, supporting its role in OM. Microinjection of pertussis toxin blocked DHP induction of OM and the progest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 49 publications
(96 reference statements)
1
31
0
Order By: Relevance
“…Expression of mPRα, the nuclear progesterone receptor (Pgr), and Pgrmc1 in the fully-grown Stage IVa immature follicles was confirmed by Western blot analysis using previously characterized polyclonal zebrafish antibodies ( 8 , 21 , 27 ). In brief, Stage IVa follicles were collected from adult zebrafish following protocols described previously ( 21 , 22 ).…”
Section: Methodsmentioning
confidence: 89%
“…Expression of mPRα, the nuclear progesterone receptor (Pgr), and Pgrmc1 in the fully-grown Stage IVa immature follicles was confirmed by Western blot analysis using previously characterized polyclonal zebrafish antibodies ( 8 , 21 , 27 ). In brief, Stage IVa follicles were collected from adult zebrafish following protocols described previously ( 21 , 22 ).…”
Section: Methodsmentioning
confidence: 89%
“…Indeed, PGRMC1-associated membrane trafficking determines the cell surface localization of a number of different proteins including e.g., epidermal growth factor receptor (Ahmed et al, 2010a), insulin receptor and glucose transporters GLUT-1 and GLUT-4 in A549 lung cancer cells (Hampton et al, 2018), glucagon-like peptide-1 (GLP-1) receptor complex in pancreatic beta cells , synaptic vesicles in the central nervous system (Izzo et al, 2014), and membrane progestin receptor α (mPRα) in rat granulosa cells (Thomas et al, 2014) and maturing zebrafish oocytes (Aizen et al, 2018). The translocation of transmembrane proteins such as membrane receptors to the cell surface could underlie much of the biology attributed to PGRMC1 (Ahmed et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…GPER was shown to regulate oocyte maturation in vitro. In carp (Cyprinus carpio) and zebrafish, maturation of cultured oocytes is regulated by estrogens and progestogens, where pharmacologic and RNA interference approaches demonstrated that estrogens inhibit maturation via GPER while progestogens promote maturation via membrane progesterone receptors [5,[27][28][29][30]. In ovaries cultured from golden hamsters (Mesocricetus auratus), estradiol promoted the formation of primordial follicles in a GPER-dependent manner [31].…”
Section: Introductionmentioning
confidence: 99%